METHODS OF TEACHING NEWLY INTRODUCED THEMES IN THE SUBJECT OF TECHNOLOGY (American Journal of Technology and Applied Sciences, 2023)
In this article, we will show you topics that have just entered the science of technology. The reasons for creating new themes are highlighted by their place and achievements in science. The use of pedagogical technologies for teaching new subjects and their effectiveness is given. In order to have a positive impact on the market economy, it is explained what products are made through these topics.